Novel concepts and engineering strategies for heterologous expression of efficient hydrogenases in photosynthetic microorganisms - Schumann, Conrad; Fernández Méndez, Jorge; Berggren, Gustav; Lindblad, Peter (Frontiers in Microbiology, 2023)
Hydrogen is considered one of the key enablers of the transition towards a sustainable and net-zero carbon economy. When produced from renewable sources, hydrogen can be used as a clean and carbon-free energy carrier, as well as improve the sustainability of a wide range of industrial processes. Photobiological hydrogen production is considered one of the most promising technologies, avoiding the need for renewable electricity and rare earth metal elements, the demands for which are greatly increasing owing to the current simultaneous electrification and decarbonization goals. Photobiological hydrogen production employs photosynthetic microorganisms to harvest solar energy and split water into molecular oxygen and hydrogen gas, unlocking the long-pursued target of solar energy storage. However, photobiological hydrogen production has to-date been constrained by several limitations. This review aims to discuss the current state-of-the art regarding hydrogenase-driven photobiological hydrogen production. Emphasis is placed on engineering strategies for the expression of improved, non-native, hydrogenases or photosynthesis re-engineering, as well as their combination as one of the most promising pathways to develop viable large-scale hydrogen green cell factories. Herein we provide an overview of the current knowledge and technological gaps curbing the development of photobiological hydrogenase-driven hydrogen production, as well as summarizing the recent advances and future prospects regarding the expression of non-native hydrogenases in cyanobacteria and green algae with an emphasis on [FeFe] hydrogenases.